2022
DOI: 10.1021/acsenergylett.2c01009
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Interdiffusion during Synthesis of Ni-Rich Core–Shell Cathode Materials

Abstract: Surface reactions between Ni-rich cathode materials and electrolytes limit the achievable specific capacity and lifetime in the high energy density Li-ion batteries based on these cathode materials. A core−shell approach, which contains a less reactive shell-phase on top of a high-capacity core-phase, can be used to reduce these surface reactions. However, interdiffusion of the elements in the core and shell phases can occur during calcination, which limits the choice of elements to be used in the shell phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…These observations further confirm B‐doping into O‐site and the existence of OLWO and LBO compounds. [ 13b,14 ] The possibility of WB reacting with LiOH is independently verified by Figure S3 (Supporting Information). The XRD results indicate that WB reacts with LiOH, possibly via the following reaction (not mass balanced for illustration purpose): LiOHbadbreak+WBLixWyOz(Li4WO5badbreak+Li6WO6) badbreak+ LixByOz(LiBO2badbreak+Li3BO3)+H2normalO\[ \begin{array}{*{20}{c}} \begin{array}{l}{\rm{LiOH}} + {\rm{WB}} \to {\rm{L}}{{\rm{i}}_{\rm{x}}}{{\rm{W}}_{\rm{y}}}{{\rm{O}}_{\rm{z}}}\left( {{\rm{L}}{{\rm{i}}_4}{\rm{W}}{{\rm{O}}_5} + {\rm{L}}{{\rm{i}}_6}{\rm{W}}{{\rm{O}}_6}} \right)\\\quad + \;{\rm{L}}{{\rm{i}}_{\rm{x}}}{{\rm{B}}_{\rm{y}}}{{\rm{O}}_{\rm{z}}}\left( {{\rm{LiB}}{{\rm{O}}_2} + {\rm{L}}{{\rm{i}}_3}{\rm{B}}{{\rm{O}}_3}} \right) + {{\rm{H}}_2}{\rm{O}}\end{array} \end{array} \] …”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…These observations further confirm B‐doping into O‐site and the existence of OLWO and LBO compounds. [ 13b,14 ] The possibility of WB reacting with LiOH is independently verified by Figure S3 (Supporting Information). The XRD results indicate that WB reacts with LiOH, possibly via the following reaction (not mass balanced for illustration purpose): LiOHbadbreak+WBLixWyOz(Li4WO5badbreak+Li6WO6) badbreak+ LixByOz(LiBO2badbreak+Li3BO3)+H2normalO\[ \begin{array}{*{20}{c}} \begin{array}{l}{\rm{LiOH}} + {\rm{WB}} \to {\rm{L}}{{\rm{i}}_{\rm{x}}}{{\rm{W}}_{\rm{y}}}{{\rm{O}}_{\rm{z}}}\left( {{\rm{L}}{{\rm{i}}_4}{\rm{W}}{{\rm{O}}_5} + {\rm{L}}{{\rm{i}}_6}{\rm{W}}{{\rm{O}}_6}} \right)\\\quad + \;{\rm{L}}{{\rm{i}}_{\rm{x}}}{{\rm{B}}_{\rm{y}}}{{\rm{O}}_{\rm{z}}}\left( {{\rm{LiB}}{{\rm{O}}_2} + {\rm{L}}{{\rm{i}}_3}{\rm{B}}{{\rm{O}}_3}} \right) + {{\rm{H}}_2}{\rm{O}}\end{array} \end{array} \] …”
Section: Resultsmentioning
confidence: 77%
“…[ 12 ] In another independent study, W was added to NCM, in which W was found to react with NCM to form LWO layer on the surface of polycrystalline NCM particles during heat treatment; the former was also found to help enhance mechanical strength. [ 13 ] However, there is no related work in the literature on simultaneously using W and B as an additive to improve the stability of SNCM and understanding the dual stabilization mechanisms. The objective of this work is to fill this knowledge gap by using WB as an additive to stabilize SNCM and concentrating on unravelling the fundamental dual stabilization mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] Massive efforts have been devoted to understanding its origins of inferior failure mechanism. [15][16][17] The dilemma of high energy delivery and extended cyclic life for Co-free cathodes is mostly caused by the anisotropic volume expansion and contraction, in particular, the abrupt lattice collapse at a high-charged state that deteriorates the structural integrity and leads to intergranular cracks. [18,19] Besides, due to the magnetic frustration effects, Co-free cathodes typically suffer from severe structure defects, so-called Li/Ni mixing, [20,21] resulting in Li ion sluggish and capacity loss.…”
mentioning
confidence: 99%
“…The elevated temperature causes significant morphological changes, like decreased particle size from dehydration and increased porosity from gas release . More importantly, in the context of the design of heterostructures, it also causes cation interdiffusion of transition metals within secondary particles when compositional gradients exist, ,, changing the elemental profile (Figure ) and challenging the control of the final architecture. A study was conducted using SEM-EDS measuring linear diffusion coefficients of Ni 3+ , Mn 3+ , and Co 3+ for increasing temperatures performed on laminar pressed pellets, due to the difficulty of measuring concentration profiles in the radial direction, which found that Co 3+ exhibited a 10× higher diffusion rate than Mn 3+ when diffusing opposite Ni 3+ .…”
mentioning
confidence: 99%